Progress of semitransparent emerging photovoltaics for building integrated applications - Zhisheng Zhou; Zhangyu Yuan; Zhipeng Yin; Qifan Xue; Ning Li; Fei Huang (Green Energy & Environment, 2024)
With the rapid development of emerging photovoltaics technology in recent years, the application of building-integrated photovoltaics (BIPVs) has attracted the research interest of photovoltaic communities. To meet the practical application requirements of BIPVs, in addition to the evaluation indicator of power conversion efficiency (PCE), other key performance indicators such as heat-insulating ability, average visible light transmittance (AVT), color properties, and integrability are equally important. The traditional Si-based photovoltaic technology is typically limited by its opaque properties for application scenarios where transparency is required. The emerging PV technologies, such as organic and perovskite photovoltaics are promising candidates for BIPV applications, owing to their advantages such as high PCE, high AVT, and tunable properties. At present, the PCE of semitransparent perovskite solar cells (ST-PSCs) has attained 14% with AVT of 22–25%; for semitransparent organic solar cells (ST-OSCs), the PCE reached 13% with AVT of almost 40%. In this review article, we summarize recent advances in material selection, optical engineering, and device architecture design for high-performance semitransparent emerging PV devices, and discuss the application of optical modeling, as well as the challenges of commercializing these semitransparent solar cells for building-integrated applications.